EVALUASI PENGGUNAAN ANTIBIOTIKA PADA PASIEN LEUKEMIA LIMFOBLASTIK AKUT DENGAN DEMAM NEUTROPENIA DI RUMAH SAKIT UMUM DAERAH ABDUL WAHAB SJAHRANIE SAMARINDA - Octaviana Maria Simbolon; Liniati Geograf (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2020)
ABSTRACT The use of antibiotics is one of the management of neutropenic fever in patients with acute lymphoblastic leukemia (ALL). Irrational and excessive antibiotics can promote resistance to certain bacteria. The aim of this study was to evaluate the use of antibiotics given to ALL patients with neutropenic fever qualitatively and quantitatively. This type of observational research was conducted with a descriptive method using a cross-sectional design. Retrospective data collection from medical records of ALL patients who received antibiotics during 2017-2018. The quality of antibiotic use was analyzed using the Gyssens method, while the quantity of antibiotic use was analyzed using the DDD method per 100 bed days. Based on the results of the study of 7 ALL patients with neutropenic fever, the rational (category 0) use of antibiotics was 50% and the irrational (category I-IV) use of antibiotics was 50%. The use of inappropriate antibiotic dose (category IIA) was 25%, the use of the antibiotic inaccurate interval of use (category IIB) was 10%, and there was no indication that antibiotic use (category V) was 15%. Quantitative evaluation of the use of antibiotics using the DDD method per 100 bed days showed that the total use of antibiotics was 7 types with a DDD value of 100 patient days of 19.15. The most widely used antibiotic is the cephalosporin class, namely cefotaxime with a DDD value of 6.51. Keywords: antibiotics, leukemia, quality, quantity